VIZIBILITATEA BIBLIOTECII MUNICIPALE ÎN MEDIUL PROFESIONAL - COȘERIU, director adjunct al BM „B.P. Hasdeu”, Tatiana (BIBLIOPOLIS, 2020)
The alignment to creative and cognitive thinking beyond the patterns consolidates the success of BM. Intelligent eff orts and ongoing trends provide persuasion and credibility to the Municipal Library „B.P. Hasdeu” in professional environment.